The principle of equal treatment between women and men in European Union law: Cautious Expansion, Member State Hesitation and a Shift in Method – The Case of Directive 2022/2381 “Women on Boards” - Florelle Moreau (Pensar)
The principle of equal treatment between women and men in EU law has gradually expanded from limited economic provisions to a broader social and professional scope. Directive 2022/2381 introduces gender quotas for listed companies that appear binding but, upon closer examination, grant significant flexibility to Member States. Transposition across Member States remains uneven, with some going beyond the directive’s requirements, and others implementing it only partially or minimally. Despite legal advances, the representation of women in top management remains low, raising concerns about the directive’s overall effectiveness. This situation reflects a broader shift from a hard legislative approach towards softer, incentive-based governance within the EU.